Методи синтезу функціоналізованих циклічних енамінонітрилів - Шемеген, Р.В.; Хиля, О.В. (Доповіді НАН України, 2025)
Розроблено низку ефективних підходів до синтезу 2-гетарил-2-(1-арил(гетарил)піролідин-2-іліден)ацетонітрилів. Запропоновані методи дають можливість варіювати як будову гетарилацетонітрильного фрагмента, так і структуру N-замісників піроліденового циклу, зокрема електронозбагачених та гетероароматичних. Піролідиновмісні сполуки виявляють широкий спектр фармакологічної активності, тому отримані продукти можуть бути використані в біологічних дослідженнях. A number of effective approaches to the synthesis of 2-hetaryl-2-(1-aryl(hetaryl)pyrrolidin-2-ylidene)acetonitriles have been developed. The methods are based on various ways of constructing the pyrrolidinylidene ring. These include the recycling of 2-hetaryl-2-(tetrahydro-2-furanilidene)acetonitriles upon interaction with aromatic amines, as well as the condensation of alicyclic and cyclic imidoyl chlorides with hetarylacetonitriles. The approaches studied allow for variation in both the structure of the hetarylacetonitrile fragment and the structure of the N-substituents of the pyrrolidin ring, including electron-rich and heteroaromatic ones. The structure of the obtained compounds has been established and confirmed by NMR spectroscopy. Pyrrolidine-containing compounds have a wide spectrum of pharmacological activity, therefore the obtained products can be considered promising compounds for biological screening.